A web based room reservation system for students of Sakura College at UNIMAS - Dgku Nor Syakirah, A Bakar (Universiti Malaysia Sarawak, (UNIMAS), 2015)
A Web Based Room Reservation System for Student of Sakura College at UNIMAS is a system that allows students to reserve a room in college residential by they own via online. The system is intended for the use of students and staffs of college residential in order to make easy in room allocating process. This proposed system only can be use after the list name of students whose successful get to stay in college residential on the next semester has been announces. Besides the college administration, only the eligible students have authorization to access the system. The system uses apartments and room image layout as a guided for users to know location of apartment or room they want to select. In addition, information such as room status, room's resident, fee and type of room provided on the image layout as user's reference. Most of functions or processes within this system are easy to use since only requires user to click button, except for registering new account by staff or user update personal information. Iterative Waterfall Model is approach that has been used and implement in developing the system which involved five important phases in this project. The model was chosen because it is suitable for developing a small-size system. Information that was used in developing the system was obtained through interviews, thesis, journal, articles and internet. Feedback regarding the system's effectiveness and design has been achieved though user testing with several student and staff of Sakura College. The user's feedback has been used as guided to correct the system's error, as well as future work for system improvements